CV Bate, grondlegger van die Potchefstroom Herald - H.S. Gouws; Johannes D. Froneman (Contree, 2012)
The British-born newspaperman CV Bate founded the Potchefstroom Herald in 1908. He remained owner for 49 years during which time he established not only the paper but himself as a journalist of some repute. As a news medium Bate’s Potchefstroom Herald covered all the major international and national events, without neglecting the community news of an ever-changing Potchefstroom. He was also a crafty businessman and compassionate member of a community that did not always share his pro-British political views. More important was his strong support for reconciliation between the Afrikaans- and English-speaking South Africans. In support of this ideal, he established an Afrikaans paper, the Westelike Stem. While Bate’s sentiments left its marks on his reporting, his integrity was above reproach and he notably gave due prominence to the victory of the National Party in 1948 and the new prime minister’s visit to Potchefstroom. Subsequent to Bate’s retirement, his papers fell into the hands of Afrikaners who eventually transformed the Potchefstroom Herald into a predominantly Afrikaans publication. But when the Potchefstroom Herald celebrated its centenary, the paper had perhaps become what Bate always intended: a non-ideological paper that tried to serve the whole community of Potchefstroom. The Potchefstroom Herald thus remains a monument to one man’s tenacity and spirit.